An Acoustic Analysis of the Relationship between Vowel Height and Tone in Dholuo (Impact: Journal of Transformation, 2026)
This study investigated the relationship between vowel height and tone in Dholuo, a Nilotic language spoken in western Kenya. Dholuo has two main dialects; this study focused on the Kisumu–South Nyanza variety. Previous research, notably Hombert (1978), suggests that vowel height may influence tonal realization, with high vowels tending to raise pitch. However, the extent and direction of this effect are known to vary across languages. To determine whether vowel height affects tonal realization in Dholuo, lexical items bearing high and low tones were selected for analysis. These items contained the low vowel /a/ and the high vowels /u/, /ʊ/, /i/, and /ɪ/. Four native speakers of Dholuo (two male and two female) participated in the study. Their productions were recorded directly into a computer using Speech Analyzer software and an external microphone. The recorded data were phonetically transcribed, after which Speech Analyzer was used to extract fundamental frequency (F0) values for the vowels, measured in Hertz (Hz). For each vowel–tone combination, the sum and mean F0 values were calculated. The results showed that differences in the pitch levels of both high and low tones across high and low vowels were not statistically significant. Nevertheless, the findings support the widely observed cross-linguistic tendency for high vowels to be associated with higher pitch, thus confirming a universal predisposition, even though this effect does not appear to be phonologically robust in Dholuo.